2022
DOI: 10.3390/polym14214713
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Electro Conductive Textiles Utilizing the Dip-Coating Technique: Their Functionality, Durability and Sustainability

Abstract: The presented review summarizes recent studies in the field of electro conductive textiles as an essential part of lightweight and flexible textile-based electronics (so called e-textiles), with the main focus on a relatively simple and low-cost dip-coating technique that can easily be integrated into an existing textile finishing plant. Herein, numerous electro conductive compounds are discussed, including intrinsically conductive polymers, carbon-based materials, metal, and metal-based nanomaterials, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 140 publications
0
18
0
Order By: Relevance
“…Previous studies have shown that thin films may be uniformly deposited on fibers using dipcoating. 195 However, the performance of fiber-shaped devices fabricated using this technology cannot be compared to the performance of conventional planar devices. The traditional white light OLED has a serial structure, and its light emitting layer (EML) is 2−3 times thicker than that of a single-color OLED, making its use in fibers challenging.…”
Section: Organic Field Effect Transistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that thin films may be uniformly deposited on fibers using dipcoating. 195 However, the performance of fiber-shaped devices fabricated using this technology cannot be compared to the performance of conventional planar devices. The traditional white light OLED has a serial structure, and its light emitting layer (EML) is 2−3 times thicker than that of a single-color OLED, making its use in fibers challenging.…”
Section: Organic Field Effect Transistorsmentioning
confidence: 99%
“…However, due to the immaturity of the structure and process, the production of optical fibers based on white OLEDs confronts remarkable challenges. Previous studies have shown that thin films may be uniformly deposited on fibers using dip-coating . However, the performance of fiber-shaped devices fabricated using this technology cannot be compared to the performance of conventional planar devices.…”
Section: Applications and Devicesmentioning
confidence: 99%
“…Particle-dispersed functional resin started to gain popularity with the increasing demand for durable coatings that can be easily processed. 82 Functional coating-based textiles could be considered as the third-generation materials in textile-based EMI shields, after metal yarn-and conducting polymer-incorporated textiles. They had several advantages over conducting-polymer incorporated textiles like tailorable property profile, enhanced durability to washing, facile coating techniques, and high chances of commercialization.…”
Section: Carried Out Electrolessmentioning
confidence: 99%
“…The same was observed in the coating domain, i.e., particles were dispersed in coating resins to produce functional coatings. Particle-dispersed functional resin started to gain popularity with the increasing demand for durable coatings that can be easily processed . Functional coating-based textiles could be considered as the third-generation materials in textile-based EMI shields, after metal yarn- and conducting polymer-incorporated textiles.…”
Section: Journey Of Textiles In Emi Shieldingmentioning
confidence: 99%
“…The literature shows extensive variation in the stoichiometry of reactants, substrate effects, dopant effects, etc., on EMI shielding properties. , The field slowly evolved by deploying lossy fillers like BaTiO 3 , Fe 3 O 4 , Co–Ni, etc., to enhance the absorption. However, most of the studies reported in the literature show EMI shielding behavior only in the lower frequency ranges. Such data are not relevant to the currently existing technologies (like 4G and 5G) which operate at much higher frequencies. The behavior of conducting polymer-modified fabrics at high frequencies would be interesting to investigate as the operating mechanisms of attenuation are different. , …”
Section: Introductionmentioning
confidence: 99%